2017
DOI: 10.1371/journal.pone.0183759
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual comparison between abdominal virtual mono-energetic spectral and conventional images using a novel spectral detector CT

Abstract: ObjectivesTo quantitatively and qualitatively assess abdominal arterial and venous phase contrast-enhanced spectral detector computed tomography (SDCT) virtual mono-energetic (MonoE) datasets in comparison to conventional CT reconstructions provided by the same system.Materials and methodsConventional and MonoE images at 40–120 kilo-electron volt (keV) levels with a 10 keV increment as well as 160 and 200 keV were reconstructed in abdominal SDCT datasets of 55 patients. Attenuation, image noise, and contrast- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The previous studies showed that low energy levels VMIs (≤60 keV) on the SDCT could obviously improve abdominal vascular contrast for higher photoelectric attenuation as the energies close to the K-edge of iodine. 8 , 21 The present study demonstrated a similar result that the attenuation of lower extremity vessels was higher at 40 to 60 keV compared with CIs. The ability to improve vascular contrast in low energy levels VMIs is useful in the circumstance of suboptimal vascular enhancement, which can avoid extra contrast medium and radiation doses brought by extra scanning and especially benefit patients with renal dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…The previous studies showed that low energy levels VMIs (≤60 keV) on the SDCT could obviously improve abdominal vascular contrast for higher photoelectric attenuation as the energies close to the K-edge of iodine. 8 , 21 The present study demonstrated a similar result that the attenuation of lower extremity vessels was higher at 40 to 60 keV compared with CIs. The ability to improve vascular contrast in low energy levels VMIs is useful in the circumstance of suboptimal vascular enhancement, which can avoid extra contrast medium and radiation doses brought by extra scanning and especially benefit patients with renal dysfunction.…”
Section: Discussionsupporting
confidence: 84%
“…Iodine concentration [mg/ml] of HR and RT was directly quantified by IntelliSpace Portal. Signal-to-noise ratio (SNR) of AZ, HR, RT and normal liver parenchyma (SNR AZ , SNR HR , SNR RT , SNR Liver ) were calculated according to the following formula as previously reported [ 23 , 39 , 40 ]: …”
Section: Methodsmentioning
confidence: 99%
“…A number of DECT approaches have been validated and deployed in the clinical environment (Movie 1). Broadly, these may be grouped into emission versus detector-based techniques [ [37] , [38] , [39] , [40] , [41] ], with major differences highlighted in Table 1 .…”
Section: Approaches To Dual Energy Ct and Image Reconstructionsmentioning
confidence: 99%